Adaptive magnetoelastic metamaterials: A new class of magnetorheological elastomers. (January 2018) - Harne, Ryan L; Deng, Zhangxian; Dapino, Marcelo J
This article reports means to significantly enhance the adaptation of static and dynamic properties using magnetorheological elastomers and demonstrates the enhancements experimentally. The tunability of traditional magnetorheological elastomers is limited by magnetic field strength and intrinsic magnetic–elastic coupling. This contrasts with recent efforts that have revealed large static and dynamic properties change in elastomeric metamaterials via exploiting internal void architectures and collapse mechanisms, although design guidelines have not been developed to adapt properties in real-time. Considering these benchmark efforts, this research integrates concepts from topologically controlled metamaterials and active magnetorheological elastomers to create and study magnetoelastic metamaterials that mutually leverage applied magnetic fields and reconfiguration of internal architectures to achieve real-time tuning of magnetoelastic metamaterial properties across orders of magnitude. Following detailed descriptions of the manufacturing procedures of magnetoelastic metamaterials, this article describes experiments that characterize the static and dynamic properties adaptation. It is found that by the new integration of internal collapse mechanisms and applied magnetic fields, magnetoelastic metamaterials can be reversibly switched from near-zero to approximately 10 kN/m in one-dimensional static stiffness and tailored to double or halve resonant frequencies for dynamic properties modulation. These ideas may fuel new research where geometry, magnetic microstructure, and structural design intersect, to advance state-of-the-art utilization of magnetorheological elastomers.